2022
DOI: 10.4103/jfmpc.jfmpc_430_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of clinical features and vaccination status in Omicron and non-Omicron infected patients during the third wave in Mumbai, India

Abstract: Objectives: The Omicron variant–mediated COVID-19 wave is responsible for a global tsunami of cases. There is scarce data about the clinical and epidemiological characteristic analyses of the third wave. We present the data of COVID-19 patients from Mumbai region during the early third wave by taking S-gene target failure (SGTF) as a proxy for probable Omicron cases. Methods: We collected retrospective data of RT-PCR-confirmed (COVID-19) patients, and measured the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Till December 2021 the number of COVID-19 cases were below 10,000 from then, India witnessed its third wave with sudden rise in incidence of COVID-19 infection with omicron variant. 7 During this period nearly 90% of Indian adult population has received at least one dose of COVID-19 vaccine but still most vaccinated individuals got re-infected with the virus. This showed that the role of vaccine in reducing the transmission of the disease was limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Till December 2021 the number of COVID-19 cases were below 10,000 from then, India witnessed its third wave with sudden rise in incidence of COVID-19 infection with omicron variant. 7 During this period nearly 90% of Indian adult population has received at least one dose of COVID-19 vaccine but still most vaccinated individuals got re-infected with the virus. This showed that the role of vaccine in reducing the transmission of the disease was limited.…”
mentioning
confidence: 99%
“…Takke et al found mild clinical symptoms in vaccinated COVID positive patients. Vaccines might not be effective against re-infection but can attenuate disease severity and mortality, as evident by high coverage of vaccination in the country 7. Unvaccinated elderly patients were more affected and had poor outcomes than younger population to support this finding, a study conducted by Sara et al concluded that Coronavirus disease 2019 (COVID-19) caused by the virus is particularly severe in older individuals because they are more likely to have an impaired immune response.…”
mentioning
confidence: 99%